2013
DOI: 10.1371/journal.pone.0057742
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lysophosphatidic Acid Receptor 1 and Relation with Cell Proliferation, Apoptosis, and Angiogenesis on Preneoplastic Changes Induced by Cadmium Chloride in the Rat Ventral Prostate

Abstract: BackgroundLysophosphatidic acid (LPA) is a phospholipid growth factor involved in cell proliferation, differentiation, migration, inflammation, angiogenesis, wound healing, cancer invasion, and survival. This study was directed to evaluate the immunoexpression of LPA-1, cell proliferation, apoptosis, and angiogenesis markers in preneoplastic lesions induced with cadmium chloride in rat prostate.MethodsThe following parameters were calculated in ventral prostate of normal rats and rats that received Cd in drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The etiology of prostate cancer development is complex and is associated with a multitude of potential contributing factors (23, 42, 43) (Table 1). Experimental evidence has shown that long-term exposure of normal human prostate epithelial cells (RWPE-1) to Cd in culture transforms them to malignant phenotypes (19, 44).…”
Section: Cadmium and Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of prostate cancer development is complex and is associated with a multitude of potential contributing factors (23, 42, 43) (Table 1). Experimental evidence has shown that long-term exposure of normal human prostate epithelial cells (RWPE-1) to Cd in culture transforms them to malignant phenotypes (19, 44).…”
Section: Cadmium and Prostate Cancermentioning
confidence: 99%
“…Lysophosphatidic acid (LPA), a phospholipid growth factor involved in a variety of cellular processes such as proliferation, differentiation, migration, inflammation, angiogenesis, wound healing, cancer invasion and survival is one of the most investigated molecules in experimental models (55-57). Cd-treated rats showed significantly higher LPA-1 expression in dysplastic lesions compared with that in normal prostate epithelium in controls (42). In addition, LPA may induce proliferation and survival of androgen-independent prostate cancer cells (55).…”
Section: Cadmium and Prostate Cancermentioning
confidence: 99%
“…Especially for prostate, Cd requires much less time than other toxicant to produce the malignantly transformation on normal prostate epithelial cells [8]. Moreover, Cd triggers the prostatic local inflammatory responses and fibrillar rearrangement, damages the prostatic balance of collagen deposition and degradation, and disturbs the homeostasis of proliferation and apoptosis [7, 9, 10]. Increased collagen deposition and prostatic fibrosis are critical factors for the development of lower urinary symptoms (LUTS) and urinary obstructive symptoms [11].…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant to the human health as cadmium is ranked as carcinogen [ 4 ], and furthermore smoke interferes either with epithelial wound healing [ 5 ] and the antioxidant/oxidant balance [ 6 , 7 ]. Both these effects have been shown to be directly or indirectly affected by Cd exposure [ 8 , 9 ].…”
Section: Heavy Metals As Risk Factors For Chronic Diseasesmentioning
confidence: 99%